Design a first level English program with a Communicative Aproach for a multicultural and multilingual classroom in the field of Sociology for URACCAN's University. - Bush, Doris Louise (España, 2012)
Enseña la importancia del inglés, la enseñanza del lenguaje comunicativo, describe las debilidades que existen en los estudiantes y docentes
Incluye retrato y tabla
Keywords: 1. IMPORTANCE OF ENGLISH 2. COMMUNICATIVE LANGUAGE TEACHING